Two new free-living nematode species of the family Xyalidae from the Laizhou Bay of the Bohai Sea, China - Sun, Yan; Huang, Yong; Tang, Hongshuo; Zang, Yu; Xiao, Hui; Tang, Xuexi (Zootaxa, 2019)
Two new species of the family Xyalidae from the Laizhou Bay of the Bohai Sea, China are described and illustrated herein. Daptonema papillifera sp. nov. is characterized by relatively small body size, L-shaped spicules with a large cephalate proximal end, triangular gubernaculum with a dorsal apophysis, 5–6 conjoint precloacal cuticularized spines and two ventral papillae located at the middle of the tail. Daptonema papillifera sp. nov. is easily distinguished from the other species in this genus by having 5–6 conjoint precloacal cuticularized spines and two ventral caudal papillae. Pseudosteineria anteramphida sp. nov. is characterized by eight groups of long subcephalic setae located posterior to amphideal fovea, curved slender spicules with cephalate proximal end and tapered distal end, tubular gubernaculum without apophysis, precloacal supplements absent, and a short precloacal seta present. In comparison with its most similar congeneric species, P. ventropapillata Tchesunov, 2000 the new species differs in having smaller body, not jointed cephalic setae, absence of precloacal supplements and absence of gubernacular apophysis.